2016
DOI: 10.1371/journal.pone.0160532
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Suppresses Leptin Gene in 3T3-L1 Adipocytes

Abstract: Leptin is a key regulator of energy intake and expenditure. This peptide hormone is expressed in mouse white adipose tissue, but hardly expressed in 3T3-L1 adipocytes. Using bisulfite sequencing, we found that CpG islands in the leptin promoter are highly methylated in 3T3-L1cells. 5-azacytidine, an inhibitor of DNA methyltransferase, markedly increased leptin expression as pre-adipocytes matured into adipocytes. Remarkably, leptin expression was stimulated by insulin in adipocytes derived from precursor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Given the induction of vaspin gene expression especially in iBAT of cold exposed mice, further analyses were carried out to elucidate potential mechanisms regulating vaspin expression. Thus, we focused on DNA methylation, a reversible epigenetic process enabling the adaption to environmental changes, which has already been shown to affect expression of other important adipokines such as leptin and adiponectin [41] , [42] , [43] . Since a decrease in promoter DNA methylation is mostly accompanied by amended binding of transcription factors (TF) and increased mRNA expression, we focused on analyzing promoter DNA methylation of the vaspin gene at binding sites for PPARγ:RXRα and TCF7L2 – both TFs involved in adipogenesis ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the induction of vaspin gene expression especially in iBAT of cold exposed mice, further analyses were carried out to elucidate potential mechanisms regulating vaspin expression. Thus, we focused on DNA methylation, a reversible epigenetic process enabling the adaption to environmental changes, which has already been shown to affect expression of other important adipokines such as leptin and adiponectin [41] , [42] , [43] . Since a decrease in promoter DNA methylation is mostly accompanied by amended binding of transcription factors (TF) and increased mRNA expression, we focused on analyzing promoter DNA methylation of the vaspin gene at binding sites for PPARγ:RXRα and TCF7L2 – both TFs involved in adipogenesis ( Supplementary Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue is a highly heterogeneous organ with cell-and depot-specific functions [35][36][37]. However, we chose 3T3-L1 differentiated adipocytes because they are a well-characterized and widely used cell line in metabolic, molecular, and endocrine studies, including studies on leptin expression levels [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also take advantage of cell lines and human mesenchymal stem cells in the study of DNA methylation in the transcriptional activation of leptin and adiponectin genes ( Kuroda et al, 2016 ; Zhang W. et al, 2016 ). On top of this, Ambati et al (2016) have also demonstrated the differential expressions of genes encoding for epigenetic regulators in VAT and SCAT in mice.…”
Section: Gender Dimorphism In Adipocyte Metabolismmentioning
confidence: 99%